Multiomics analysis of serial PARP inhibitor treated metastatic TNBC inform on rational combination therapies - Labrie, Marilyne; Li, Allen; Creason, Allison; Betts, Courtney; Keck, Jamie; Johnson, Brett; Sivagnanam, Shamilene; Boniface, Christopher; Ma, Hongli; Blucher, Aurora; Chang, Young Hwan; Chin, Koei; et al. (NPJ precision oncology, 2021)
In a pilot study, we evaluated the feasibility of real-time deep analysis of serial tumor samples from triple negative breast cancer patients to identify mechanisms of resistance and treatment opportunities as they emerge under therapeutic stress engendered by poly-ADP-ribose polymerase (PARP) inhibitors (PARPi). In a BRCA-mutant basal breast cancer exceptional long-term survivor, a striking tumor destruction was accompanied by a marked infiltration of immune cells containing CD8 effector cells, consistent with pre-clinical evidence for association between STING mediated immune activation and benefit from PARPi and immunotherapy. Tumor cells in the exceptional responder underwent extensive protein network rewiring in response to PARP inhibition. In contrast, there were minimal changes in the ecosystem of a luminal androgen receptor rapid progressor, likely due to indifference to the effects of PARP inhibition. Together, identification of PARPi-induced emergent changes could be used to select patient specific combination therapies, based on tumor and immune state changes.